ความเป็นชายที่มีอำนาจนำในโฆษณารถยนต์กระบะของไทยที่ออกอากาศทางโทรทัศน์ - หาญพานิช, ศิวรัฐ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
Four television commercials for pickup trucks in Thailand were textually analyzed for hegemonic masculinity, a current configuration of practice legitimizing male dominant position in society and justifying the subordination of women. After narrative and semiology were examined, these commercials were found to contain culturally normative ideals producing examplars of masculinity. Protagonists were heroic symbols of hegemonic masculinity as masters of dominance, control, and daring. With technology seen as a masculine culture, pickup trucks as marketed have embedded meanings of body and mind. Well-built, strong bodies relate to masculine ideals, whereas mind relates to feminine subordination and compliance.